PENINGKATAN MOTIVASI BELAJAR IPA MELALUI IMPLEMENTASI METODE INQUIRY SISWA KELAS V SEKOLAH DASAR - Mahlianurrahman Mahlianurrahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the low motivation of students in grade V SD Negeri Pasi Pinang. This study aimsto describe the effort to improve students' learning motivation through the use of inquiry methods and toincrease learning motivation through the use of inquiry method in science subjects. The type of this research isclassroom action research, the subject of this research is the students of class V SD Negeri Pasi Pinang whichamounted to 24 students. The object of this research is the improvement of students' learning motivation inscience subjects. The results showed that the use of inquiry method can improve the motivation of students ingrade V SD Negeri Pasi Pinang. This can be seen from the average score of students' learning motivation incycle I is 60.2%, in cycle II increases with score 70.5%, and cycle III increases with score 92.8%. based on theresults of these studies indicate that the student's learning motivation every cycle has increased after appliedinquiry method.